(untitled) (Journal of Management and Social Sciences, 2019)
The Chilean experiments of formulating and implementing capitalist and socialist economic development strategies in the late 50s through early 70s form the core of this study. Because of the commitment of the United States Government to the development and protection of private property interests and mutatis mutandis, direct foreign investments in the Third World, Dr. Salvador Allende’s comprehensive programme of socialising the means of production in Chile from 1970â€“1973 engendered United States Government’s hostile reactions, contributing to Chile’s â€œinvisible economic blockadeâ€, and eventually, a violent overthrow of the Allende Presidency through a bloody coup de’tat on September 11, 1973. The study highlighted the lessons to be learnt from the Allende socialist experiment by any Third World country.